Penggunaan Mixed Method pada Penelitian PAI - M, Nurhidaya; Hermina, Dina; Huda, Nuril; Sumiati, Sumiati (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2024)
A good understanding of research methodology is key to generating quality knowledge, supporting informed decision-making and advancing areas of science and innovation. The use of Mixed Method in research has the advantage that it can support the process of achieving the research objectives that have been designed, of course the results are expected to be more accurate. Mixed Method in terms of time of course requires a long time in its implementation in order to really get maximum results. If previously discussed more about the gap between qualitative and quantitative, now switch to uniting / synergizing the two. The synergy of these two research approaches is then known as mixed method research. This synergy is expected to foster new power in conducting research. Research in the field of Islamic Education requires a lot of comprehensive studies so that Mixed Method can be used in conducting research on Islamic Education research topics. There are several PAI research topics that could have used the Mixed Method approach including Islamic Religious Teaching Methods, The Effect of Islamic Religious Education on Behavior and Attitudes, Learning the Quran and Hadith, Islam-Based Character Education, Islamic Religious Education in a Multicultural Context, The Role of Teachers in Islamic Religious Education, Islamic Religious Education Curriculum Development, Islamic Religious Education and Technology, Critical Analysis of Contemporary Issues in Islam. Some steps that can be taken in implementing Mixed Method are identifying research objectives, designing research studies, identifying variables, choosing qualitative and quantitative methods, developing research instruments, collecting data, analyzing data, interpreting results and communicating findings.